Monitoring of ant species surrounding the ports of South Korea - Dayeong Kim; Heejo Lee; Nanghee Kim; Beom-jun Jang; Dong Eon Kim (Biodiversity Data Journal, 2025)
The introduction and spread of invasive insects is accelerating worldwide owing to human activities, such as trade and transportation development; in particular, ports are hubs and routes for invasive insects, including ants. We surveyed ant populations in eight ports from 2021 to 2023 using pitfall traps. A total of 316,975 ants belonging to four subfamilies, 26 genera and 44 species were identified as Tetramorium tsushimae, Lasius niger, Brachyponera chinensis and Nylanderia flavipes. The statistical analysis showed that the highest values by index were for the Incheon Port (0.25), the diversity index was for the Daesan Port (2.00), the evenness index was for the Daesan Port (0.71) and the richness index was for the Gamman Port (2.13). Non-metric multidimensional scaling analysis (NMDS) indicated that ants around the Ports of Gamman, Ulsan and Gwangyang had more dominant species than those around the other ports. Five species of alien ants, including Solenopsis invicta, Solenopsis geminata, Paratrechina longicornis, Trichomyrmex destructor and Nylanderia bourbonica were identified at Gamman Port, Paratrechina longicornis at Ulsan Port and Gwangyang Port. This study provides comprehensive insights into the distribution and status of ants around ports, offering foundational data for the early detection of alien ants to reduce the risk of their settlement and spread and to respond proactively.